2009
DOI: 10.30638/eemj.2009.013
|View full text |Cite
|
Sign up to set email alerts
|

Radiolytic Output of Hydrogen as Environmentally Friendly Energy Vector

Abstract: This study deals with the radiolytical decomposition of water molecules, in the presence of some catalysts, getting out hydrogen as unpolluting and cheaper energy vector. Instead of the spent nuclear fuel elements taken out from nuclear power plants, as irradiation source it was used the 60 Co radionuclide having a specific activity of 1.1 . 10 5 Ci. It was observed that the radiolytic yield of resulted molecular hydrogen from water radiolysis in the presence of used catalysts decreased as: NH 4 -ZSM-5 > Pt 2+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…A variety of recent studies have shown that the radiolysis of water at the interface of solid nanoparticles is very interesting from a fundamental science aspect. Water exposed to ionizing radiation will decompose into a number of radical and molecular products (e aq – , H • , OH • , HO 2 • , H 2 O 2 , and H 2 ) . Solid surfaces often alter the yield of products from water radiolysis as compared to the bulk liquid.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of recent studies have shown that the radiolysis of water at the interface of solid nanoparticles is very interesting from a fundamental science aspect. Water exposed to ionizing radiation will decompose into a number of radical and molecular products (e aq – , H • , OH • , HO 2 • , H 2 O 2 , and H 2 ) . Solid surfaces often alter the yield of products from water radiolysis as compared to the bulk liquid.…”
Section: Introductionmentioning
confidence: 99%
“…The experiments proceeded as it follows (Cecal et al, 2008;Hauta et al, 2009): different amounts of each catalyst were weighed and introduced in 50 ml bottles, over which 30 ml distilled water were added. Then the glass vials were sealed with rubber cork, paraphyned outside and subjected to various doses of radiation energy.…”
Section: Experimental Partmentioning
confidence: 99%